Spotlight on certolizumab pegol in the treatment of axial spondyloarthritis: efficacy, safety and place in therapy - Marin, Josefina (Open Access Rheumatol, 2018)
Certolizumab pegol (CZP) is a pegylated humanized tumor necrosis factor-α inhibitor (TNFi) approved for the treatment of ankylosing spondylitis (AS) in the USA and for AS and non-radiographic axial spondyloarthritis (nr-axSpA) in Europe and in some Latin American countries. CZP lacks Fc region, preventing complement fixation and cytotoxicity mediated by antibody; CZP does not actively cross the placenta, unlike other TNFi. RAPID-axSpA study is a Phase III trial conducted in patients with AS and nr-axSpA as double blind and placebo controlled to week 24, dose blind to week 48 and open label to week 204. Of a total of 325 patients recruited, 107 patients were assigned to placebo and 218 patients to CZP (111 to CZP 200 mg Q2W, 107 to CZP 400 mg Q4W). Improvements in axial involvement, joint involvement, enthesitis and quality of life were reported in patients treated with CZP. Safety profile was like that reported for other TNFi in axSpA patients. In this article, we summarized the pharmacology and we reviewed the efficacy and tolerability of this drug for the treatment of axSpA. Some special considerations of CZP during pregnancy are included. CZP, the latest TNFi to be approved, showed efficacy in all manifestations of AS and nr-axSpA.